The effect of long-term hypogonadism on body composition and morphometry of aged male Wistar rats - Borbélyová, V; Šarayová, V; Renczés, E; Čonka, J; Janko, J; Šebeková, K; Štefíková, K; Ostatníková, D; Celec, P (Physiological research, 2021)
Clinical studies show that hypogonadism in the aging male is associated with obesity and osteoporosis. Experimental studies are mostly conducted on relatively young adult animals and the induced hypogonadism lasts for a relatively short time. The present study aimed to describe the effect of long-term hypogonadism beginning in puberty on body composition, morphometry, and bone mineral density in aged male rats. Morphometric measurements and dual-energy X-ray absorptiometry were conducted at the age of 30 months on control and gonadectomized males. Long-term hypogonadism did not affect body weight, but led to a higher fat mass (by 26 %), lower lean mass (by 44 %), shorter body length (by 9 %), and anogenital distance (by 26 %), as well as to lower tail circumference (by 15 %) in comparison to control males. Lower bone mineral density (by 13 %) and bone mineral content (by 15 %) were observed in gonadectomized males. Results showing sarcopenic obesity and osteoporosis in this model of long-term hypogonadism might mimic the situation in aging males better than the widely used short-term hypogonadism induced in young animals. The morphometric analysis could potentially be a useful tool to study normal weight obesity without the need for specific equipment.
Keywords: Animals; hypogonadismus; Rats, Wistar; Age Factors; orchiektomie; testosteron; kostní denzita; Bone Density; Obesity; Time Factors; časové faktory; věkové faktory; Orchiectomy; Adiposity; adipozita; Osteoporosis; Hypogonadism; obezita; Male; složení těla; modely nemocí na zvířatech; Disease Models, Animal; krysa rodu Rattus; Body Composition; Testosterone; zvířata; mužské pohlaví; sarkopenie; osteoporóza; Sarcopenia; Rats; potkani Wistar